Cognitive behaviour therapy for depression and anxiety in Parkinson's disease - Egan, Sarah; Laidlaw, K.; Starkstein, S. (IOS Press, 2015)
Evidence is reviewed demonstrating that cognitive behavior therapy (CBT) is effective in the treatment of depression and anxiety in Parkinson’s disease. The aims were to review the extant literature, specify a model of cognitive and behavioral maintenance factors in depression and anxiety in Parkinson’s disease and provide a guide to treatment. It is argued that treatment should take into account specific cognitive and behavioral maintaining factors. Symptoms of depression and anxiety are highly prevalent in Parkinson’s disease and therapists should consider how to augment the efficacy of CBT for patients with Parkinson’s disease. Cognitive and behavioral interventions can help people overcome some of the challenges in living with PD by maximizing wellbeing and overall quality of life. Parkinson’s Disease (PD) is a common, chronic and progressive neurological condition associated with negative impact on quality of life, disability and increased mortality [1, 2]. We have recently outlined a rationale for considering the use of cognitive behavior therapy (CBT) for treatment of depression and anxiety in Parkinson’s disease [3]. The current paper adds a new element to the literature by proposing a conceptual framework for applying CBT for depression and anxiety in PD. The paper also addresses strategies for overcoming barriers to treatment engagement in PD.